8.6k views
3 votes
In Exercise,Use properties of exponents to simplyfy the expression.
(e2/3)(e3)

User ZMabrook
by
6.6k points

1 Answer

2 votes

Answer:
e^{(11)/(3)}

Explanation:

According to the Multiplication property of exponents :
a^m\cdot {a^n}=a^(m+n)

For example :
2^7\cdot 2^5= 2^(7-5)=2^2

Let's take one more example ,
a^(-11)\cdot a^(1)=a^(-11+1)=a^(-10)

The given expression :
(e^{(2)/(3)})(e^3)

By Multiplication property of exponents , we have


(e^{(2)/(3)})(e^3)=e^{(2)/(3)+3}


=e^{(2+3(3))/(3)}=e^{(2+9)/(3)}


=e^{(11)/(3)}

Hence, the simplified expression is
e^{(11)/(3)} .

User Forrert
by
5.0k points